2015
DOI: 10.1093/hmg/ddv261
|View full text |Cite
|
Sign up to set email alerts
|

NovelPOC1Amutation in primordial dwarfism reveals new insights for centriole biogenesis

Abstract: POC1A encodes a WD repeat protein localizing to centrioles and spindle poles and is associated with short stature, onychodysplasia, facial dysmorphism and hypotrichosis (SOFT) syndrome. These main features are related to the defect in cell proliferation of chondrocytes in growth plate. In the current study, we aimed at identifying the molecular basis of two patients with primordial dwarfism (PD) in a single family through utilization of whole-exome sequencing. A novel homozygous p.T120A missense mutation was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…The growth parameters, facial dysmorphism and skeletal features of the proband in this report are highly similar to other published cases (Koparir et al 2015), and although the large majority of patients reported to date are of prepubertal age, one other patient has been described with precocious puberty (Koparir et al 2015), which may play a role in the short final height of the proband we describe. There are significant phenotypic differences among patients reported to date, however, Most prominently, the proband we describe had no ectodermal dysplasia, reported in three of four families to date (Koparir et al 2015; Shaheen et al 2012), and, conversely, did have extreme, dyslipidaemic insulin resistance, which was not clearly described in other reports. Differing genetic backgrounds may contribute to these differences, as suggested by the occurrence of type 2 diabetes of onset in middle age in several members of the family we describe, albeit without the extreme insulin resistance of the proband.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The growth parameters, facial dysmorphism and skeletal features of the proband in this report are highly similar to other published cases (Koparir et al 2015), and although the large majority of patients reported to date are of prepubertal age, one other patient has been described with precocious puberty (Koparir et al 2015), which may play a role in the short final height of the proband we describe. There are significant phenotypic differences among patients reported to date, however, Most prominently, the proband we describe had no ectodermal dysplasia, reported in three of four families to date (Koparir et al 2015; Shaheen et al 2012), and, conversely, did have extreme, dyslipidaemic insulin resistance, which was not clearly described in other reports. Differing genetic backgrounds may contribute to these differences, as suggested by the occurrence of type 2 diabetes of onset in middle age in several members of the family we describe, albeit without the extreme insulin resistance of the proband.…”
Section: Discussionsupporting
confidence: 89%
“…We identified 7 rare, functional homozygous variants, among which was a frameshift mutation in POC1A , which was associated during the course of our study by three groups with a similar syndrome in five consanguineous families from the Middle East (Koparir et al 2015; Sarig et al 2012; Shaheen et al 2012). Three of these families harboured one of two missense mutations (Koparir et al 2015; Sarig et al 2012), while the other three families had in common an early nonsense mutation, although cellular studies suggested significant translational readthrough of the mutation (Shaheen et al 2012). …”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations